The Story of Jewish Polygamy - Goldfeder, Mark (Columbia Journal of Gender and Law, 2014)
This Article examines the intersection of law, religion, and culture in the evolution of polygamy in the Jewish tradition. It traces the development of Jewish thought on polygamy over time by assembling and analyzing relevant discussions, arguments, decisions, and biblical interpretations from the time of the Hebrew Bible passages, when plural marriage was an accepted part of Jewish society, to the early Middle Ages when the practice was formally and conclusively rejected. In doing so, the Article attempts to untangle the various influences—both practical and doctrinal, internal and external—on the evolution of marriage law in Jewish communities. These findings highlight the mutable nature of marriage norms within a religious community, the adaptability of religious doctrine to the practical needs of the community, and the potentially progressive force of religious morality in advancing women’s rights.